Acellular dermal matrices as an adjunct to implant breast reconstruction: Analysis of outcomes and complications. Issue 4 (April 2020) - Tasoulis, Marios-Konstantinos; Teoh, Victoria; Khan, Ayesha; Montgomery, Catherine; Mohammed, Kabir; Gui, Gerald
Abstract: Purpose: Acellular dermal matrices (ADM) are increasingly used in implant-based breast reconstruction (IBR). Uncertainty remains with regard to their efficacy and complications. The aim of this study was to evaluate the outcomes and complication rates associated with the use of ADMs in IBR. Methods: Retrospective cohort study of patients undergoing ADM-assisted IBR between 2008 and 2013. Cases were identified from a prospectively collected database. Simple descriptive statistics and logistic regression analysis were performed. Results: A total of 110 patients (175 mastectomies) were included in the analysis. The median age was 46 (19–75) years and the median BMI was 22.2 (16.2–41.5). Seventy nine mastectomies were performed for therapeutic purposes. The median mastectomy weight was 244 (185–335) gr. The majority of reconstructions were performed with fixed volume (n = 115, 66%) or permanent expandable implants (n = 53, 30%) as one-stage procedures. Forty mastectomies were associated with at least one complication. The infection rate was 2.3% (n = 4). Post-operative haematoma developed in 5 cases (2.9%), but only 2 required surgical interventions. Three mastectomies were complicated by nipple necrosis (3.6%), 3 with skin necrosis (1.7%) and 9 with wound dehiscence (5.1%). The capsule formation rate was 2.3% (n = 4). Reconstruction failure with implant loss occurred in 3 cases (1.7%). Conclusions: The complication rates following ADM-assisted IBR can be very low with appropriate patient selection and meticulous surgical technique. This supports the safety of using ADM in carefully selected patients. Further research is warranted to assess the health economics of ADM use in IBR.